Mídia e terror: a construção da imagem do terrorismo no jornalismo - Paiero, Denise Cristine (2012)
This research investigates how the news media influences, strengthens and enlarges the image of the terrorist acts in the 21th century. It also analyzes how the so-called terrorists use journalism as a tool and how they plan their acts based on certain trends of contemporary media coverage. The main problem here is: how terrorism uses the mass media to extend the state of terror, broadening terrorist actions? Our hypothesis is that the so-called terrorists get hold of some tendencies of the media, like the spectacle, the manichaeism and the homogenization of content, and rely on key elements of culture to develop their actions. In turn, to fulfill its obligation to inform, within the context of journalism-spectacle, journalism is subordinated to that strategy, helping to feed the subsequent discourse of terror and the feeling of menace. This thesis approaches the communication environment formed between terrorism - press - society and its complex relationship. It uses concepts of Semiotics of Culture, whose main representative is the author Ivan Bystrina, and Media Theory, from the german communicologist and journalist Harry Pross. Based on these theories, we work with elements of the archeology of media in order to understand the most elementary structures that are present in construction, impact and assimilation of terrorist acts. This paper aims to bring out the symbolic structures that underlie the discourse of terrorism in order to turn it into newsworthy facts, and also how the news media echoes and amplifies these acts, either by repetition of information, either by how these questions are treated by journalists. It's a known fact that in this communication environment, there is a constant feedback between the news agent and the media itself. For this investigation we used the major terrorist events of our time, focusing on the most influential, as the attacks of September 11th, 2001, in the U.S., of July 7th, 2005, in London, and of March 11th, 2004, in Madrid. In Brazil, we focused on the episode known as the "Day of the PCC", which happened on May 15th, 2006, in São Paulo. Veja magazine and the newspaper Folha de S. Paulo are the main documental sources for our analyzes. We also used other media, national and foreign, as working material